Psychological well-being and academic performance of Ukrainian medical students under the burden of war: a cross-sectional study - Korda, Mykhaylo; Shulhai, Arkadii; Shevchuk, Oksana; Shulhai, Oleksandra; Shulhai, Anna-Mariia (Frontiers in Public Health, 2025)
IntroductionThe mental health of medical students is a key factor for academic performance and the delivery of high-quality medical care in the future. Globally, medical students face numerous challenges that can affect their education. Living and studying facing the war has a crucial influence on medical students’ education and daily life. The study aimed to determine the psychological well-being and academic achievements of Ukrainian medical students who lived in the rear areas after the 18 months of the Russian–Ukrainian war.MethodsThe cross-sectional study was conducted at I.Ya. Horbachevsky Ternopil National Medical University. We analyzed the psychological well-being and educational achievements of medical students from the second to fifth year of Medical Faculty using the self-report scales DASS-21 and IES-R. A total of 776 students filled out the DASS-21 scale and 491 IES-R scale, respectively.ResultsFollowing the first 18 months of the war, 62.5, 59.6, and 58.8% of Ukrainian medical students self-reported signs of stress, anxiety, and depression, respectively. Severe and extremely severe depressive symptoms were observed in 25.6% of students, anxiety in 31.9%, and stress in 29.7%, with a higher prevalence among female students. Additionally, 44.2% of responders had significant symptoms of post-traumatic stress disorder, with the highest scores on the hyperarousal subscale (>37). Academic performance in 2023 was significantly lower compared to the pre-war period in 2019 (p < 0.001) (p = 0.000). The multiple linear regression analysis showed that academic performance was positively associated with depression (p = 0.003), hyperarousal (p < 0.001), anxiety (p = 0.03), and negatively associated with stress (p = 0.002).ConclusionUkrainian medical students in rear areas are facing various challenges, with war-related stressors having a profound impact on their mental health. Our findings have shown an increasing prevalence of anxiety, stress, depression, and symptoms of post-traumatic stress disorder, all of which may negatively affect academic performance. The educational process during wartime is important for facilitating qualified medical personnel and quality healthcare. Understanding the burden of war allows for the development of wellness programs that support student mental health in conflict zones.